2014
DOI: 10.1590/s2179-975x2014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term physiological responses to copper stress in Salvinia auriculata Aubl.

Abstract: Aim: To evaluate, in a short-time exposure, the physiological responses of Salvinia auriculata Aubl. under different concentrations of Cu. Methods: The plants were exposed to treatments with 0.01, 0.1, 1 and 10 mM of Cu in a period of 2 days. Then development variables of S. auriculata (weight, photosynthetic pigments, and soluble carbohydrate), lipid peroxidation (malondialdehyde, aldehydes, and electrolyte leakage) and production of antioxidants (anthocyanins, carotenoids, flavonoids, and proline) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 45 publications
1
26
1
3
Order By: Relevance
“…Moreover, some related studies have reported an increase in the total amount of flavonoids and anthocyanins in Salvinia sp. exposed to metal(loids) indicating that these compounds could be involved in metal tolerance described for these aquatic ferns [19,23,50]. However, in our study, no increase in antioxidant pigments content was observed, possibly because the amount of Cu, Cd, Pb, and Zn accumulated into S. biloba leaves was not detrimental at the oxidative level.…”
Section: Evaluation Of Metal Phytotoxicity In S Bilobacontrasting
confidence: 43%
See 2 more Smart Citations
“…Moreover, some related studies have reported an increase in the total amount of flavonoids and anthocyanins in Salvinia sp. exposed to metal(loids) indicating that these compounds could be involved in metal tolerance described for these aquatic ferns [19,23,50]. However, in our study, no increase in antioxidant pigments content was observed, possibly because the amount of Cu, Cd, Pb, and Zn accumulated into S. biloba leaves was not detrimental at the oxidative level.…”
Section: Evaluation Of Metal Phytotoxicity In S Bilobacontrasting
confidence: 43%
“…Anthocyanin content was determined according to [23]. Briefly, plant samples (50.0 mg FW) were incubated with 5.0 mL of methanol:HCl (99:1) and kept in the dark for 24 h. The extract was then centrifuged at 2500× g for 10 min.…”
Section: Determination Of Antioxidants Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bizzo et al [14] in experiments with Salvinia auriculata Ablu. cultures at lower concentrations of copper (0.01 and 0.1 mM Cu) after 2 days obtained 430.2 (79% of initial value) and 495.4 (91%) g of chlorophyll a/g of fresh matter (control: 544.7 g of chlorophyll a/g of fresh matter), 193.2 (94%) and 216.0 (105%) g of chlorophyll b/g of fresh matter (control: 205.4 g of chlorophyll b/g of fresh matter) and 632.4 (84%) and 711.3 (95%) g of total chlorophyll/g of fresh matter (control: 750.2 g of total chlorophyll/g of fresh matter).…”
Section: Resultsmentioning
confidence: 98%
“…Bizzo et al [14] investigated the influence of Cu in various concentrations (0.01, 0.1, 1 and 10 mM) on the development of Salvinia auriculata Ablu., in a short-time exposure of plants (2 days). The results have shown high tolerance of Salvinia auriculata Ablu.…”
Section: Introductionmentioning
confidence: 99%